FACTORS AFFECTING WORK STRESS AMONG EMPLOYEES AT PT. MARINDA UTAMAKARYA SUBUR DELI SERDANG BRANCH - Khairiyah Dwie Vanesa; Fatma Indriani; Reni Agustina Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Work stress is a global problem with around 450 million people affected according to WHO, with stress levels in the Asia Pacific region reaching 48%. This study aims to analyze the factors that influence work stress in employees of PT. Marinda Utamakarya Subur, Deli Serdang Branch. The research method uses an analytical study with a quantitative approach and cross-sectional design. The study population includes all employees of PT. Marinda Utamakarya Subur, Deli Serdang Branch with a total sampling technique, so that the sample size is 36 people. Data analysis uses the Mann Whhitney, Kruskal Wallis, and Spearman tests. The results showed that there was no significant correlation between age and work stress (r = -0.028; p = 0.871) and education level with work stress (p = 0.190). While there was a significant correlation between workload and work stress (r = 0.410; p = 0.013) with a moderate negative correlation, gender with work stress ( p = 0.042) where male employees tend to experience higher work stress, and length of service with work stress (p = 0.015) with a tendency for employees who work more than 4 years to have higher stress levels. The conclusion of the study shows that gender, length of service and workload are significant factors that influence work stress and age and education status do not have a significant effect on work stress in employees of PT. Marinda Utamakarya Subur, Deli Serdang Branch.